Factors Associated with Caesarean Section Among Women Delivered at Kirehe District Hospital - Habiyakare Caste; Rutayisire Erigene (Journal of Public Health International, 2022)
The aim of this study is determine the prevalence and factors associated with caesarean section among women delivered at Kirehe District Hospital. A retrospective study was conducted among women delivered at Kirehe District Hospital from January 2018 to December 2019. The medical files of all women delivered at the hospital who meet the inclusion criteria were reviewed. Data were checked for completeness, cleaned, coded and entered into excel sheet, and then exported to SPSS version 22.0 for further analysis. Descriptive statistics was used to estimate the prevalence and description of study participants. Multivariable logistic regression models were used to estimate risk for CS with 95% confidence intervals (CIs). The study was conducted in accordance with the research protocol Mount Kenya University Rwanda research ethical committee. The majority 806 (69.9%) of women who delivered at Kirehe district hospital from January 2018 to December 2019 were aged 22-35 years old. The prevalence of C-section at Kirehe District Hospital was 23.1%. Demographic and economic factors associated with Caesaren section in bivariate and multivariate analysis was respondent’s type of health insurance where women who used private health insurance were 3 times more likely to deliver by C-section. The findings from multivariate analysis revealed that women who experienced eclampisa had 45% risk of C-Setion compared to those without Eclampsia. Women in rural area of Rwanda seem to have increased access to and use of CS. However, the significant increase in the rate of CS is of concern due to the potential of unnecessary CS.
Keywords: Cesarean section